2009
DOI: 10.1111/j.1468-1293.2008.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term antiretroviral therapy to prevent mother‐to‐child transmission is safe and results in a sustained increase in CD4 T‐cell counts in HIV‐1‐infected mothers*

Abstract: BackgroundShort-term antiretroviral therapy (START) to prevent mother-to-child transmission (MTCT) is currently recommended for all HIV-1-infected pregnant women. The objective of this study was to assess the effect on CD4 cell counts and viral load dynamics the withdrawal of START after birth could generate. MethodsThis was a 5-year cohort study involving HIV-1-infected pregnant women who presented with CD4 counts 4300 cells/mL and had received START to prevent MTCT. ResultsSeventy-five pregnancies were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
4
6
0
Order By: Relevance
“…This data is consistent with another recent study from Brazil in pregnant women with CD4+ counts > 300 cells/mm 3 on HAART for MTCT, in which it took a mean of 3.5 years for CD4+ counts to fall below 300 cells/mm 3 (16). More durable immune reconstitution was found in those with higher baseline CD4+ and greater CD4+ response to HAART during pregnancy, while more rapid CD4+ decline was associated with prior ARV exposure and detectable viral load during prophylaxis.…”
Section: Discussionsupporting
confidence: 92%
“…This data is consistent with another recent study from Brazil in pregnant women with CD4+ counts > 300 cells/mm 3 on HAART for MTCT, in which it took a mean of 3.5 years for CD4+ counts to fall below 300 cells/mm 3 (16). More durable immune reconstitution was found in those with higher baseline CD4+ and greater CD4+ response to HAART during pregnancy, while more rapid CD4+ decline was associated with prior ARV exposure and detectable viral load during prophylaxis.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, 20% of 75 HIV+ pregnant women in a Brazilian cohort with similar immunologic status (median CD4+ 573 cells/mm 3 ) who initiated tARVp had CD4+ decline to <300 cells/mm 3 within 24 months after discontinuing prophylaxis [12]. Comparisons of CD4+ decline among women who either discontinued tARVp at delivery or continued have yielded conflicting results: over a short follow-up period of 6 months postpartum, women who discontinued tARVp had a higher rate of decline compared to women who continued ART regimens in a Brazilian cohort [13].…”
Section: Discussionsupporting
confidence: 90%
“…Although the immunological response is physiologically compromised during pregnancy and a decrease in the CD4TL count is usually observed [15], no significant difference was found between the mean value of these cells and the pregnancy stage in the present study, which has also been observed in other studies [16, 17]. …”
Section: Discussionsupporting
confidence: 82%